Red blood cell transfusions in the neonate - Santos, Amélia Miyashiro Nunes dos; Trindade, Cleide Enoir Petean [UNESP] (American Academy of Pediatrics (AAP), 2011)
Despite recent trends to decrease allogeneic red blood cell (RBC) transfusion thresholds, such transfusions remain an important supportive and life-saving intervention for neonatal intensive care patients. In neonates, apart from concerns about transfusionassociated infections, many controversial questions regarding transfusion practices remain unanswered. Moreover, neonates present specific clinical and immunologic characteristics that require selected blood component products. This article addresses many of these issues from a medical perspective, with emphasis on the best blood banking techniques to provide RBC products for neonatal transfusions. Copyright © 2011 by the American Academy of Pediatrics.